2013
DOI: 10.1542/peds.2012-2586
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Preventive Dental Visits in Reducing Nonpreventive Dental Visits and Expenditures

Abstract: BACKGROUND AND OBJECTIVE: Although preventive dental visits are considered important for maintaining pediatric oral health, there is relatively little research showing that they reduce subsequent nonpreventive dental visits or costs. At least 1 study seemed to find that early preventive dental care is associated with more restorative and emergency visits. Previous studies are limited by their inability to account for unmeasurable factors that may lead children to “select” into using both more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…(Savage et al 2004; Sen et al 2013) These findings extend over the life course, reducing overall disease experience into adulthood. (Bhaskar et al 2014) However, receipt of recommended preventive visits is still generally low for US children, and not all children attend PDV at equal rates.…”
Section: Introductionmentioning
confidence: 96%
“…(Savage et al 2004; Sen et al 2013) These findings extend over the life course, reducing overall disease experience into adulthood. (Bhaskar et al 2014) However, receipt of recommended preventive visits is still generally low for US children, and not all children attend PDV at equal rates.…”
Section: Introductionmentioning
confidence: 96%
“…One of the major health care challenges in the prevention and treatment of dental caries is access to an oral health care system, which includes both a defined approach to prevention and providers to treat established lesions [Sen et al, 2013]. Dental caries is a preventable disease, and a recognized community-based preventive approach is water fluoridation [Parnell et al, 2009].…”
mentioning
confidence: 99%
“…Although there is uncertain evidence in regards to the effectiveness of educative programs in avoiding caries development 30 , studies have shown that early preventive dental care is cost-effective and can reduce the need of further restorative treatment, mainly in highrisk populations 1,29,31,32 .…”
Section: Discussionmentioning
confidence: 99%